Literatur Review : Terapi Nonfarmakologis Kompres Aloe Vera sebagai Upaya Penanganan Demam pada Anak - Shabrina Safitri; Richa Cahya Setyowati; Nurkhalisah; Anisa Duwi Putri; Ni Wayan Wiwin Asthiningsih (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Fever in children is an increase in body temperature caused by infection that requires appropriate management to prevent complications. One non-pharmacological therapy that can be used is an Aloe vera compress. This literature review aimed to determine the effectiveness of Aloe vera compress therapy in reducing body temperature in children with fever. The method used was a literature review conducted through article searches in the Google Scholar, PubMed, Garuda, and SINTA databases published between 2021 and 2026. Of the 80 articles identified, 10 articles met the inclusion criteria and were analyzed. The review results showed that Aloe vera compress therapy was effective in helping reduce children’s body temperature, with temperature reductions ranging from 0.1°C to 2.5°C. The effectiveness was influenced by the child’s condition, the cause of fever, the duration of the intervention, and the area of compress application. The mechanism of Aloe vera compress therapy works through its cooling effect, high water content, and conduction process that facilitates heat transfer from the body. In addition to reducing body temperature, this therapy also improved children’s comfort during fever. Therefore, Aloe vera compress therapy can be used as a safe, natural, and easily applicable supportive non-pharmacological intervention in the management of fever in children.